2009
DOI: 10.2308/aud.2009.28.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Audit Fees for Initial Audit Engagements Before and After SOX

Abstract: SUMMARY: Legislators, regulators, and the media have expressed concerns that auditors “lowball” the fees for initial-year audits and that such fee discounts can lead to reduced audit quality. We hypothesize that initial-year audit fee discounts will be less likely in the post-SOX period than in the pre-SOX period. Using both fee-levels and fee-changes models, we find that Big 4 clients receive initial-year audit fee discounts of about 24 percent in 2001; this finding is consistent with results from many prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 14 publications
9
75
2
3
Order By: Relevance
“…Second, we follow prior audit pricing studies (e.g., Huang, Raghunandan, & Rama, 2009;Kim, Liu, & Zheng, 2012;Dao, Raghunandan, & Rama, 2012;Fung, Gul, & Krishnan, 2012) to construct the audit pricing regression model as follows:…”
Section: Women Audit Partner and Audit Feesmentioning
confidence: 99%
“…Second, we follow prior audit pricing studies (e.g., Huang, Raghunandan, & Rama, 2009;Kim, Liu, & Zheng, 2012;Dao, Raghunandan, & Rama, 2012;Fung, Gul, & Krishnan, 2012) to construct the audit pricing regression model as follows:…”
Section: Women Audit Partner and Audit Feesmentioning
confidence: 99%
“…In fact, almost all of the studies mentioned in the literature review either use archival data -in many cases publicly available data -(for example, Krishnan, 2003 ;Francis et al , 2005 ;Knechel et al , 2007 ;Krishnan et al , 2008 ;Huang et al , 2009 ) or use experiments to test hypotheses. In the experimental settings, the subjects are typically auditors (for example, Solomon et al , 1999 ).…”
Section: Original Articlementioning
confidence: 99%
“…Consistent with these explanations, the results of recent (post-SOX) literature show that second-tier auditors have become more conservative in the sense that, although in the pre-SOX period they tolerated earnings management to a greater extent by clients that switched from a Big 4 auditor, in the post-SOX period they are associated with lower earnings management ( Krishnan et al , 2008 ). The fi ndings of Huang et al (2009) , however, suggest that Big 4 fi rms have also become more conservative in the post-SOX period with respect to both their new client acceptance and their pricing decisions (for example, the Big 4 fi rms are much less likely to serve as a successor following a client ' s dismissal of the predecessor in the post-SOX period than in the pre-SOX period, and they now earn an initial fee premium instead of the initial fee discount observed in the pre-SOX period).…”
Section: Accounting Fi Rm Alumnimentioning
confidence: 99%
See 1 more Smart Citation
“…He reported that the level of audit fees could increase in client firms' size, operation complexity, and inherent audit risk because more quantity of resources utilized by the auditor in performing the audit examination would be needed and auditors were exposed to larger possible litigation risks when auditing become more complex. After controlling these three groups of fee determinants, subsequent studies explored additional audit fee determinants including auditor size, non-audit services, auditor change, auditor change direction, auditor brand name and industry specialization, client satisfaction, client risks, client bargaining power, audit committee characteristics, internal control quality, SOX passage, crosslisting and country's legal regimes, education requirement for new accountants, and audit market competition (Sohn, 2011;Palmrose 1986aPalmrose , 1986bFrancis & Simon 1987;Simon & Francis 1988;Craswell et al, 1995;Behn et al, 1999;Craswell & Francis, 1999;Johnstone & Bedard, 2001;Whisenant et al, 2003;Abbott et al, 2003;Ashbaugh et al, 2003;Chaney et al, 2004;Hay et al, 2006, Huang et al, 2007Hogan & Wilkins, 2008;Huang et al, 2009;Choi et al, 2009;Allen & Woodland, 2010, Hay & Knechel 2010Fudenberg & Tirole, 1995;Hoitash et al, 2008).…”
Section: Introductionmentioning
confidence: 99%